HUBUNGAN KADAR ENZYM KHOLINESTERASE DENGAN KADAR HORMON THYROID PADA WUS DI DAERAH GONDOK ENDEMIK - Sukati S.; Suryati K.; M. Ichsan; Mucherdiyantiningsih Mucherdiyantiningsih; Djoko Kartono (Persagi, 2006)
The Relationship Between Cholinesterase Enzym and Iodine Status of Child Bearing Age Woman (CBAW) In The Endemic Goitre Area.Background: Pesticide as a pollutant substance is a goitrogenic agent. It can form a strong complex bound with iodine in the body. Women who ive in the endemic goiter, area where the iodine source in the nature is limited and frequently exposed by pesticide, can increase the prevalence of iodine deficiency disorder (IDD).Objectives: To find out the relationship between cholinesterase enzyme concentration (as an indicator of pesticide exposure in the body) and iodine status of women in the endemic goiter area.Methods: The study was conducted in Pakis sub district, Magelang Regency, Central Java on July to November 2005. The design of the research was